Robotic Services at Home: An Initialization System Based on Robots' Information and User Preferences in Unknown Environments. (30th July 2014) - Mohd, Nor Nur Safwati; Mizukawa, Makoto
One important issue in robotic services is the construction of the robotic system in the actual environment. In other words, robots must perform environment sensing or have information on real objects, such as location and 3D dimensions, in order to live together with humans. It is crucial to have a mechanism to create an actual robotic system (intelligent space) such that there is no initialization framework for the objects in the environment, or we have to perform SLAM and object recognition as well as mapping to generate a useful environmental database. In intelligent space research, normally the objects are attached to various sensors in order to extract the necessary information. However, that approach will highly depend on sensor accuracy and the robotic system will be burdened if there are too many sensors in an environment. Therefore, in this paper we present a system in which a robot can obtain information about an object and even create the furniture layout map for an unknown environment. Our approach is intended to improve home-based robotic services by taking into account the user or individual preferences for the Intelligent Space (IS). With this information, we can create an informational map of the home-based environment for the realization of robot assistance of humans in their daily activities at home, especially for disabled people. The result shows the system design and development in our approach by using model-based system engineering.